ANALISIS SEMIOTIKA PEIRCE: POSTER IKLAN MCDONALD’S SERI FATHER’S DAY - Akbar, M. Aditya Zuhri; Pratishara, Gibbran; Wibowo, Arif Ardy (Universitas Ahmad Dahlan, 2023)
The purpose of this research is to determine the meaning contained in the McDonald's Father's Day series advertising posters. The type of this research is descriptive with a qualitative approach. The researcher uses Charles Sanders Peirce's semiotic analysis, which focuses on signs and markers, to determine the meaning contained in the poster. According to the research results, the McDonald's poster series Father's Day celebrates Father's Day through the Burger Buns image, which represents a father figure. The text